Brassinosteroids Antagonize Jasmonate-Activated Plant Defense Responses through BRI1-EMS-SUPPRESSOR1 (BES1). Issue 2 (27th November 2019) - Liao, Ke; Peng, Yu-Jun; Yuan, Li-Bing; Dai, Yang-Shuo; Chen, Qin-Fang; Yu, Lu-Jun; Bai, Ming-Yi; Zhang, Wen-Qing; Xie, Li-Juan; Xiao, Shi
Abstract : A key transcription factor antagonizes JA-activated plant defense responses by suppressing the expression of defensin and glucosinolate biosynthesis genes. Abstract: Brassinosteroids (BRs) and jasmonates (JAs) regulate plant growth, development, and defense responses, but how these phytohormones mediate the growth-defense tradeoff is unclear. Here, we identified the Arabidopsis ( Arabidopsis thaliana ) dwarf at early stages1 ( dwe1 ) mutant, which exhibits enhanced expression of defensin genes PLANT DEFENSIN1.2a ( PDF1.2a ) and PDF1.2b . The dwe1 mutant showed increased resistance to herbivory by beet armyworms ( Spodoptera exigua ) and infection by botrytis ( Botrytis cinerea ). DWE1 encodes ROTUNDIFOLIA3, a cytochrome P450 protein essential for BR biosynthesis. The JA-inducible transcription of PDF1.2a and PDF1.2b was significantly reduced in the BRASSINOSTEROID INSENSITIVE1-ETHYL METHANESULFONATE-SUPPRESSOR1 ( BES1 ) gain-of-function mutant bes1- D, which was highly susceptible to S. exigua and B. cinerea . BES1 directly targeted the terminator regions of PDF1.2a/PDF1.2b and suppressed their expression. PDF1.2a overexpression diminished the enhanced susceptibility of bes1- D to B. cinerea but did not improve resistance of bes1- D to S. exigua . In response to S. exigua herbivory, BES1 inhibited biosynthesis of the JA-induced insect defense-related metabolite indolic glucosinolate by interacting with transcription factors MYB DOMAIN PROTEIN34 (MYB34), MYB51, and MYB122 and suppressing expression of genes encoding CYTOCHROME P450 FAMILY79 SUBFAMILY B POLYPEPTIDE3 (CYP79B3) and UDP-GLUCOSYL TRANSFERASE 74B1 (UGT74B1). Thus, BR contributes to the growth-defense tradeoff by suppressing expression of defensin and glucosinolate biosynthesis genes.